The Gamelan in the Catholic Liturgy in Yogyakarta - Luca Pietrosanti (IJCAS (International Journal of Creative and Arts Studies), 2019)
This paper is a brief overview of the use of the gamelan together with the polyphonic choir in the Roman rite of Holy Mass. Through the examination ofrepertoires, interviews and active participation in rehearsals and Masses, thiswork illustrates the types of compositions of liturgical music for gamelan aswell as the way these compositions are used. Particular attention is addressedto some key-concepts of traditional gamelan music, such as gending, benthuk,laras, pathet, garap. It will be apparent that these concepts are adapted, firstlyto integrate the gamelan with a vocal element, the choir (which is based on awestern tradition) and secondly, to meet the needs of the rite of Holy Mass.Although indirectly, this paper also represents a paradigm of “Inculturation”,which describes a process distinct from “Enculturation”. The term“Inculturation” must be intended as “the incarnation of the Gospel in nativecultures and also the introduction of these cultures into the life of the Church”,so defined by the Pope John Paul II in the encyclical Slavorum Apostoli, 2ndJune 1985, VI-21. Instead, with the term “Enculturation” we intend the processby which an individual learns the traditional content of a culture andassimilates its practices and values. Thus, the two words represent twodifferent processes of assimilation of culture.